Clinical value of an adenosine triphosphate-based chemotherapy response assay in resectable stage III colorectal cancer - Kim, Chan Dong (Ann Surg Treat Res, 2019)
PURPOSE: ATP-based chemotherapy response assay (ATP-CRA) is a well-documented and validated technology that can individualize chemotherapy. This study was undertaken to assess the usefulness of ATP-CRA in advanced colorectal cancer (CRC) patients receiving adjuvant chemotherapy. METHODS: A total of 136 patients with curative resection between January 2006 and April 2014 were evaluated using ATP-CRA. Patients received either the FOLFOX or Mayo clinic regimen chemotherapy following assay results. The sensitive-group (S-group) was defined as a drug-producing ≥ 40% reduction in ATP, and the resistant-group (R-group) as an ATP reduction of < 40%. These 2 groups were further subdivided to produce 4 subgroups: the FOLFOX sensitive subgroup (the FS subgroup [n = 65]), the Mayo sensitive subgroup (the MS subgroup [n = 40]), the FOLFOX resistant subgroup (the FR subgroup [n = 10]), and the Mayo resistant subgroup (the MR subgroup [n = 21]). Clinical responses and survival results were compared for both treatment regimens. RESULTS: The FS and MS subgroups showed a better disease-free survival rate (29% vs. 40%, 35% vs. 47.6%) and overall survival rate (92.3% vs. 80.0%, 87.5% vs. 76.2%) than FR and MR subgroups. The FS and MS subgroups showed a longer time to relapse (20.2 months vs. 9.5 months, 17.6 months vs. 16.4 months) than the FR and MR subgroups. CONCLUSION: ATP-CRA tailored-chemotherapy has the potential to provide a survival benefit in resectable advanced CRC.